Repositioning peer marking for feedback literacy in higher education. Issue 8 (17th November 2021) - Fernández-Toro, María; Duensing, Annette
Abstract: While the benefits of peer review on feedback literacy are widely recognised, peer marking tends to be associated with summative assessment, and often dismissed as a legacy from outdated approaches where assessment was used for measuring learning rather than as a means of achieving it. This paper repositions peer marking as a means of developing feedback literacy within a sustainable model of assessment. It presents an illustrative study where formative peer marking was integrated in a first-year distance learning undergraduate module in language studies, using digital asynchronous tools. Student engagement among the cohort ( N  = 939), as well as students' learning behaviours and attitudes to peer marking, were evaluated through a combination of quantitative and qualitative methods. Patterns of student engagement varied, with 41% of the cohort engaging in some way, but only 17% completing all task components. Thematic analysis of student forum discussions reveals that the process of marking and comparing marks did elicit an array of critical evaluation strategies among the latter group. Comments voiced by those students as to the value of peer marking were also positive, though it is also noted that this was a self-selected group. A roadmap for the graded integration of peer assessment across the curriculum is proposed.